A novel approach to assess balneotherapy effects on musculoskeletal diseases - an open interventional trial combining physiological indicators, biomarkers, and patients’ health perception - Silva, Jani (2023)
The present study aimed to evaluate whether a 14-day period of balneotherapy influences the inflammatory status, health-related quality of life (QoL) and quality of sleep, underlying overall health state, and clinically relevant benefits of patients with musculoskeletal diseases (MD). The health-related QoL was evaluated using the following instruments: 5Q-5D-5L, EQ-VAS, EUROHIS-QOL, B-IPQ, and HAQ-DI. The quality of sleep was evaluated by a BaSIQS instrument. Circulating levels of IL-6 and C-reactive protein (CRP) were measured by ELISA and chemiluminescent microparticle immunoassay, respectively. The smartband, Xiaomi MI Band 4, was used for real-time sensing of physical activity and sleep quality. MD patients improved the health-related QoL measured by 5Q-5D-5L (p < 0.001), EQ-VAS (p < 0.001), EUROHIS-QOL (p = 0.017), B-IPQ (p < 0.001), and HAQ-DI (p = 0.019) after balneotherapy; the sleep quality was also improved (BaSIQS, p = 0.019). Serum concentrations of IL-6 were markedly decreased after the 14-day balneotherapy (p < 0.001). No statistically significant differences were observed regarding the physical activity and sleep quality data recorded by the smartband. Balneotherapy may be an effective alternative treatment in managing the health status of MD patients, with a decrease in inflammatory states, along with positive effects on pain reduction, patient’s functionality, QoL, quality of sleep, and disability perception status.